The Impact of the Independent Curriculum Implementation on Student Learning Outcomes in Physical Education, Sports, and Health at SMAN 19 Garut - Maulana, Cecep Ilham; Permadi, Asep Angga; Hermawan, Irwan; Sonjaya, Azhar Ramadhan (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. This study aims to ascertain (1) the efficacy of the Independent Curriculum implementation at SMAN 19 Garut; (2) the actual student learning outcomes in Physical Education at SMAN 19 Garut; (3) the impact of the Independent Curriculum implementation on student learning outcomes in Physical Education at SMAN 19 Garut; Materials and methods. This study employs a quantitative research methodology utilizing a descriptive technique. This research employs the correlation method with a simple linear regression analysis strategy. The study's subjects comprised 37 responders from the X IPS 1 class at SMAN 19 Garut. This study employed a questionnaire to gather data on the Implementation of the Independent Curriculum (Variable X) and Student Learning Outcomes in PJOK Subjects (Variable Y), along with documentation to acquire general information about the school. Results. The findings of this study are as follows: (1) The implementation of the Independent Curriculum at SMAN 19 Garut is categorized as High; (2) The student learning outcomes in PJOK subjects at SMAN 19 Garut are also categorized as High; (3) There exists an influence of the Independent Curriculum implementation on student learning outcomes in PJOK subjects at SMAN 19 Garut, evidenced by a calculated t value of 4.596, which exceeds the t table value of 2.042, and a determination coefficient of 43%. The implementation of the Independent Curriculum significantly influences student learning. Conclusion. outcomes in Physical Education at SMAN 19 Garut, highlighting the necessity of a more adaptable curriculum tailored to student requirements to enhance the quality of educational results. Schools and educators are encouraged to enhance the execution of the Independent Curriculum and to do regular assessments and refinements to maximize its effectiveness in reaching student learning outcomes.